2017
DOI: 10.1371/journal.pone.0175224
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of invasive pneumococcal disease (IPD) in adults after introduction of pneumococcal 13-valent conjugate vaccine in Spain

Abstract: A prospective laboratory-based multicenter study that collected all adult invasive pneumococcal disease (IPD) episodes from 6 Spanish hospitals before (2008–2009) and after (2012–2013). The 13-valent pneumococcal conjugate vaccine (PCV13) licensure was conducted in order to analyze the impact of PCV13 introduction for children on adult IPD. A total of 1558 IPD episodes were detected. The incidence of IPD decreased significantly in the second period by -33.9% (95% CI, -40.3% to -26.8%). IPD due to PCV7 serotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…The broadest PPV and PCV vaccines include 23 (e.g., Pneumovax) and 13 (e.g., Prevnar 13) serotypes, respectively. While the CPS-based vaccines have substantially reduced invasive pneumococcal disease (IPD) in the countries where the vaccines are used (9), their impact is in part hampered by limited coverage of pathogen serotypes. A recent carriage study in children revealed that, after introduction of PCVs, many new isolates with non-PCV13 capsular types have emerged (e.g., types 22F, 12F, 33F, 24F, 15C, 15B, 23B, 10A, and 38) (10).…”
mentioning
confidence: 99%
“…The broadest PPV and PCV vaccines include 23 (e.g., Pneumovax) and 13 (e.g., Prevnar 13) serotypes, respectively. While the CPS-based vaccines have substantially reduced invasive pneumococcal disease (IPD) in the countries where the vaccines are used (9), their impact is in part hampered by limited coverage of pathogen serotypes. A recent carriage study in children revealed that, after introduction of PCVs, many new isolates with non-PCV13 capsular types have emerged (e.g., types 22F, 12F, 33F, 24F, 15C, 15B, 23B, 10A, and 38) (10).…”
mentioning
confidence: 99%
“…Current prevention of pneumococcal infections is based on vaccination and vaccines are serotype-dependent, offering protection against a subset of known serotypes. Only 13 serotypes are included in the conjugate vaccine with the highest available valency, PCV13; its widespread use changed the worldwide serotype distribution [1]. During a multicentre study, a clonal replacement was observed among invasive pneumococci of serotype 11A (not included in PCV13), associated with the emergence of β-lactam resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococci can invade sterile sites causing different invasive pneumococcal diseases (IPD) such as bacteraemic pneumonia, meningitis or primary bacteraemia. Furthermore, pneumococci cause other non-invasive diseases such as acute otitis media in children or acute exacerbations of COPD in adults [1,2]. The polysaccharide capsule, which presents one of more than 97 serotypes, is the main virulence factor and its diversity has been associated with differences in invasiveness and mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotype prevalence varies significantly in different countries and in different seasons [9]. It also has a cycling pattern every 3-5 years.…”
Section: Discussionmentioning
confidence: 99%